A Religious Patient and Her Sleep Problems: Reflections on an Experience in which Sleeping Pills were not Prescribed - Thiago Henrique Roza (University Library System, University of Pittsburgh, 2017)
The spirituality, cultural beliefs and religion of any patient are likely to have an impact on his/her health, and well-being. Health professionals, mainly young physicians and medical students, often fail to consider this type of background when taking care of their patients. This experience is a report of an interesting encounter, in the field of mental health, in which the spiritual beliefs and socioeconomic needs of a patient were considered during her treatment. Consequently, sleeping pills were not prescribed in her case.